2013
DOI: 10.1111/evj.12108
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive determination of atrial fibrillation cycle length by atrial colour tissue Doppler imaging in horses

Abstract: Tissue Doppler imaging allows noninvasive measurement of AFCL in horses with AF and is able to identify spatial differences within the equine atria. Atrial fibrillation cycle length is an indicator of atrial electrical remodelling and is an important parameter to study AF pathophysiology or the effect of antiarrhythmic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 35 publications
(41 reference statements)
2
32
0
Order By: Relevance
“…The AFCL measured in the left atrial free wall from the right parasternal 4‐chamber view was shorter compared to the other views, as has been described previously . The AFCL from this view did not show a significant increase after sotalol administration.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The AFCL measured in the left atrial free wall from the right parasternal 4‐chamber view was shorter compared to the other views, as has been described previously . The AFCL from this view did not show a significant increase after sotalol administration.…”
Section: Discussionsupporting
confidence: 78%
“…The atrial fibrillatory rate was assessed from tissue Doppler velocity curves of the atrial myocardial walls, as described previously . In brief, tissue Doppler images were acquired from the left atrial free wall in a right parasternal 4‐chamber view, from the right atrial dorsal wall at the level of the tuberculum intervenosum in a right parasternal view and from the left atrial free wall in a left parasternal long axis view.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AFCL EGM measurements were performed in the right atrium, while most AFCL TDI measurements were performed in the left atrium. A left‐to‐right gradient of atrial fibrillatory rate has been described previously in horses, with significantly shorter AFCL in the left atrial free wall compared with the right atrial wall . These spatial differences might explain the bias between AFCL EGM and AFCL TDI measurements.…”
Section: Discussionmentioning
confidence: 53%
“…The main limitation of this study is the absence of data on the repeatability of AFCL measurements, although the variability of TDI measurements of atrial contractile function has previously been demonstrated to be low to moderate, and AFCL measurements by TDI have been validated against AFCL measurements by intracardiac EGM . It cannot be excluded that the effect of sedation seen in this study is in fact a time‐related placebo effect, because measurements with sedation were always performed after those without sedation.…”
Section: Discussionmentioning
confidence: 88%